The application of an explanatory factor analysis to investigate the inter-relations amongst joint movement during performance of a football skill - Smith, C.; Gilleard, W.; Hammond, J.; Brooks, L. (Journal of Sports Science & Medicine, 2006)
Many studies have investigated the kinematics of sports skills with the majority describing the kinematics of the technique or investigating significant kinematic variables that affect performance. Many sports skills are complex three-dimensional movements involving many joints. However, few studies have investigated the relationships between kinematic variables during performance of such skills. The aim of this study was to investigate the inter- relationships among three-dimensional kinematic variables during performance of a lofted instep soccer kick. A motion analysis system was used to collect kinematic data for 13 skilled amateur soccer players attempting a standardised lofted instep kick. Three-dimensional angular displacement patterns were reported for the thoracolumbar spine and right hip joints. Two-dimensional angular displacement data was reported for the right knee and ankle joints. An exploratory rather than confirmatory factor analysis was applied, as there is currently no established theory regarding the kinematics of a lofted instep kick. Factors were extracted using the Maximum Likelihood Solution and orthogonally rotated using Varimax with Kaiser normalisation. The inter-relationship among biomechanical variables within the seven extracted factors was analysed with each factor revealing previously unknown inter-relationships among variables for different aspects of the kick. The use of exploratory factor analysis has shown the complex three-dimensional kinematic inter-relationships for a lofted instep kick. An understanding of these relationships could prove useful to coaches when instructing, and in the development of coaching programmes related to the lofted instep kick.